A role for endothelial cells in radiation-induced inflammation. (4th March 2018) - Boström, Martina; Kalm, Marie; Eriksson, Yohanna; Bull, Cecilia; Ståhlberg, Anders; Björk-Eriksson, Thomas; Hellström Erkenstam, Nina; Blomgren, Klas
Abstract: Purpose: To unravel the role of the vasculature in radiation-induced brain tissue damage. Materials and methods: Postnatal day 14 mice received a single dose of 10 Gy cranial irradiation and were sacrificed 6 h, 24 h or 7 days post-irradiation. Endothelial cells were isolated from the hippocampus and cerebellum using fluorescence-activated cell sorting, followed by cell cycle analysis and gene expression profiling. Results: Flow cytometric analysis revealed that irradiation increased the percentage of endothelial cells, relative to the whole cell population in both the hippocampus and the cerebellum. This change in cell distribution indicates that other cell types are more susceptible to irradiation-induced cell death, compared to endothelial cells. This was supported by data showing that genes involved in endothelial cell-specific apoptosis (e.g. Smpd1 ) were not induced at any time point investigated but that genes involved in cell-cycle arrest (e.g. Cdkn1a ) were upregulated at all investigated time points, indicating endothelial cell repair. Inflammation-related genes, on the other hand, were strongly induced, such as Ccl2, Ccl11 and Il6 . Conclusions: We conclude that endothelial cells are relatively resistant to ionizing radiation but that they play an active, hitherto unknown, role in the inflammatory response after irradiation. In the current study, this was shown in both the hippocampus, where neurogenesis and extensive cell death after irradiation occurs, and in the cerebellum, where neurogenesis no longer occurs at this developmental age.